2015
DOI: 10.1155/2015/254868
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported ADHD Symptoms and Interhemispheric Interaction in Adults: A Dimensional Approach

Abstract: The present study applied the dimensional approach to test whether self-reported symptoms of Attention Deficit/Hyperactivity Disorder (ADHD) in adults are associated with the speed of interhemispheric interaction. A sample of first grade students (N = 112) completed Conners' Adult ADHD Rating Scales and letter matching reaction time tasks. In the tasks, participants had to match a single target letter displayed below the fixation cross, either on left or right visual field, with one of two letters displayed ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
2
4
0
Order By: Relevance
“…The present results also indicated that in 10-week-old SHRs, volume reduction of the mPFC persisted, but only in the right hemisphere. This observation might confirm atypical brain laterality observed earlier in adult patients with ADHD (right hemisphere deficit) (Mohamed et al 2015). Moreover, a recent review of fNIRS studies has reported that right hemisphere asymmetry in atypical neuronal function was found in children with ADHD (Doi and Shinohara 2017).…”
Section: Discussionsupporting
confidence: 90%
“…The present results also indicated that in 10-week-old SHRs, volume reduction of the mPFC persisted, but only in the right hemisphere. This observation might confirm atypical brain laterality observed earlier in adult patients with ADHD (right hemisphere deficit) (Mohamed et al 2015). Moreover, a recent review of fNIRS studies has reported that right hemisphere asymmetry in atypical neuronal function was found in children with ADHD (Doi and Shinohara 2017).…”
Section: Discussionsupporting
confidence: 90%
“…A further support to the conclusion that less LVF advantage reflected reduced right hemisphere processing is that group differences were only found in the shape matching condition tapping right hemisphere specialization. This conclusion is in concert with many findings in the literature indicating a right hemisphere dysfunction together with intact or even faster interhemispheric interaction in individuals with ADHD ( Carter et al, 1995 ; Sandson et al, 2000 ; Stefanatos and Wasserstein, 2001 ; Brown and Vickers, 2004 ; Rolfe et al, 2007 ; Song and Hakoda, 2012 ; Mohamed et al, 2015 ).…”
Section: Discussionsupporting
confidence: 88%
“…The association between interhemispheric connectivity modulation and inattention symptomatology in the current sample was unexpected, as the literature around the role of interhemispheric connectivity in selective or sustained attention is sparse, both in reference to ADHD and more broadly. A large segment of the interhemispheric attention literature focuses on the integration of visual information presented to different hemifields ( Akin et al, 2014 ; Plow et al, 2014 ; Mohamed et al, 2015 ), in which interhemispheric attention performance is either downstream of more general attentional variation or is a separate phenomenon; these perspectives do not necessarily shed light on how our connectivity findings are related to the broader set of behaviors that are reflected in the Connors ADHD Inattention scale. Banich has proposed one model of attention that could provide a framework for following up on the role of altered interhemispheric interaction in ADHD ( Banich, 1998 ).…”
Section: Discussionmentioning
confidence: 99%